STUDI KOMPARATIF PELAKU TINDAK PIDANA NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DAN HUKUM ISLAM - Wahyu Akbar Prantoko; Rachmat Ihya (INTELIGENSIA MEDIA, 2024)
This research examines how drug criminal sanctions are implemented against violators inaccordance with Law no. 35 of 2009 concerning Narcotics and how to apply sanctions accordingto Islamic law. Research from the library includes this research. Research findings show that theapplication of penalties in Law no. 35 of 2009 concerning Narcotics towards perpetrators of drugcrimes relating to Articles 116, 121, 133 and 134. The findings of this research also show that thepunishment of ta'zir, as stipulated in Islamic law, can be imposed on those who commit drug- related offences. According to the judge's policy, there are several types of punishment for ta'zir, including beatings, detention, publication, punishment in the form of property, and others. He believes that this form of punishment can have a deterrent effect on both the perpetrator and otherpeople. Both the use of illegal substances and drug laws are prohibited. Similar to the prohibitionof drinking alcoholic beverages according to certain hadiths and the holy Koran, narcotics and the consumption of illegal drugs are also prohibited. Apart from that, some academics think thereare sanctions.